Emancipation Through Communicative Action: The Habermas's Critical Reading Of Dialética do Esclarecimento And The Exhaustion Of The Emancipatory Program Of Horkheimer And Adorno - Jorge A. Lubenow (Aufklärung, 2014)
This article aims to expose the critical Jurgen Habermas's point of view regarding to Dialética do Esclarecimento and the exhaustion of the emancipatory program of Horkheimer and Adorno. It intends to make clear as the Dialética do Esclarecimento leads to an impasse of an selfpointed critique of the Reason (I). In following it shows how much this selfpointed critique dues to Nietzsche and what ways Niestzsche and Horkheimer & Adorno propose to go out of this impasse (II), and the Habermas's critique of Horkheimer & Adorno point of view (III). The main texts used are O discurso filosófico da modernidade (cap. 5: “O entrosamento entre o mito e o iluminismo: Horkheimer e Adorno”) and Teoria de la acción comunicativa (cap. 4: “De Lukács a Adorno: racionalização como reificação”).